Initial considerations for height categories as a replacement of weight categories in senior taekwondo athletes - Kazemi, M.; Hetherington, A.; Ahmadi, F.; Duncan, S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. Taekwondo (TKD) like many combat sports utilizes weight as a measure to categorize competitors. In an attempt to gain advantage over opponents, athletes practice rapid weight loss to qualify for the lowest weight class possible. This practice is routine despite being fundamentally dangerous to the health of athletes. Height is a measurement that cannot be exploited for competitive advantage and has the potential to be a healthier alternative for sport classifications. Purpose and aim. This study evaluated the relationship between weight and height categories in classifying competitive senior TKD athletes for the potential of using height as a healthier grouping method. Methods. The height and weight of 118 male (n=83) and female (n=35) athletes were measured by either physical measurement during weigh-in at the Canadian National Taekwondo Championships (n=31) or following Covid-19 restrictions, athletes (n=87) were given an online survey for height and weight. The athletes were categorized by sex and senior Olympic weight category. The athletes were then grouped by 4 proposed height categories based on CDC height weight growth charts. Results. We found that 80.72% of male athletes remained within ±1 category when categorized by height and 94.29% of female athletes remained within ±1 category when categorized by height. Conclusions. Height categorization does little to disrupt current competition cohorts while disincentivizing unhealthy rapid weight loss practices in TKD athletes and providing more equitable competition by matching athletes of similar height and reach.